Application of benchmarking in the operations of RTE - Liu, Fang (Харківський національний автомобільно-дорожній університет, 2024)
The qualification paper improves theoretical principles for the implementation of benchmarking in the operations of RTE. A definition of the term "benchmarking" is proposed. The process of conducting benchmarking at RTEs has been further developed using the IDEF0 functional modeling methodology. Methodological principles for conducting benchmarking in RTEs are enhanced, which, unlike existing ones, are based on assessing competitors through the elements of the "7P" marketing mix adapted to the specifics of road transport enterprises. Strategies for enterprise operations based on each element of the "7P" marketing mix are proposed, alongside relevant recommendations for improving RTE performance. Forecast assumptions regarding the development of the research object – the use of competitors' best practices at road transport enterprises for developing and improving elements of the marketing mix.
Keywords: benchmarking; marketing mix; competitive advantages; competitive benchmarking; process approach; process; evaluation; strategy